CAPOW: a standalone program for the calculation of optimal weighting parameters for least‐squares crystallographic refinements. Issue 1 (14th December 2017) - Johnson, Natalie T.; Ott, Holger; Probert, Michael R.
Abstract : A new standalone program to calculate optimized values for weighting parameters, CAPOW, is presented along with enhanced visualization tools for analysing statistical distributions of data. Abstract : The rigorous analysis of crystallographic models, refined through the use of least‐squares minimization, is founded on the expectation that the data provided have a normal distribution of residuals. Processed single‐crystal diffraction data rarely exhibit this feature without a weighting scheme being applied. These schemes are designed to reflect the precision and accuracy of the measurement of observed reflection intensities. While many programs have the ability to calculate optimal parameters for applied weighting schemes, there are still programs that do not contain this functionality, particularly when moving beyond the spherical atom model. For this purpose, CAPOW (calculation and plotting of optimal weights), a new program for the calculation of optimal weighting parameters for a SHELXL weighting scheme, is presented and an example of its application in a multipole refinement is given.